Inhibitor of pan class-I PI3K induces differentially apoptotic pathways in acute leukemia cells: Shedding new light on NVP-BKM120 mechanism of action. (October 2016) - Bashash, Davood; Safaroghli-Azar, Ava; Delshad, Mahda; Bayati, Samaneh; Nooshinfar, Elaheh; Ghaffari, Seyed H.
Abstract: Complex interplay of intracellular signaling networks, spanning from the extracellular environment to the nucleus, orchestrate normal cell growth and survival. Dysregulation of such signals contributes to malignant transformation, thereby giving the cancer cells a survival advantage, but also could be exploited for new anticancer interventions. The aim of this study was to investigate the effects of pan class-I PI3K inhibitor NVP-BKM120 on two distinct acute leukemia cell lines, NB4 (with mutant p53) and Nalm-6 (with wild-type p53). Our data highlighted the efficacy of the inhibitor against APL and pre B ALL cell lines; however, we failed to find an obvious correlation between p53 status and the sensitivity of leukemic cells to NVP-BKM120. Real-time PCR analysis revealed a significant up-regulation of p53 target genes in Nalm-6 cells, indicating a p53-dependent mechanism involved in NVP-BKM120 cytotoxicity. On the other hand, cytotoxic effects in mutant p53-expressing NB4 cells seem to be mediated mostly by the inhibition of the PI3K/Akt/NF-κB axis. In conclusion, we suggest NVP-BKM120 induces apoptosis through p53-dependent and -independent mechanisms, indicating the potential application of the inhibitor in both wild-type and deficient p53-expressing leukemic cells.